DISTINGUISHING SYNONYMS IN ENGLISH: NUANCES AND CONTEXTUAL USAGE - Ergasheva Sabohat; Badalova Shahnoza (TADQIQOTLAR, 2026)
Abstract: Synonymy is one of the most complex aspects of the English language. While dictionaries may define two words as having the same meaning, they are rarely interchangeable in every context. This article explores the linguistic boundaries of synonyms, focusing on how emotional intensity, collocation, and register distinguish them. A special emphasis is placed on the adverb "badly" and its diverse collocational patterns to illustrate how synonym choice affects grammatical and semantic accuracy.